Relationship between reversible reasoning and conceptual knowledge in composition of function. (April 2020) - Ikram, M; Purwanto,; Parta, I N; Susanto, H
Abstract: The aim of this study was to investigate relationship between reversible reasoning and conceptual knowledge, particularly, mental action deployed by undergraduate students in reasoning reversible in problem situation of composition of function. This case study compares reversible reasoning of three high-achieving undergraduate student. These students were tested before with test measuring their understanding of aspect function. Data collected through think aloud and clinical interviews depict strategies that the participants used to work back to find original function. The result showed that constructing reversible reasoning requires conceptual knowledge with several characteristics (relational-harmonic, relational-visual, relational-pseudo) that explored in detail. Suggestion for further inquiry on improving knowledge about reversible reasoning as mental valuable tools for students in classroom practice.